SPORTS AND TECHNOLOGY: THE FUTURE OF PERFORMANCE ANALYTICS AND COACHING - Ismatov, Abdukodir (Журнал иностранных языков и лингвистики, 2024)
The intersection of sports and technology has significantly transformed the way athletes train, perform, and recover. One of the most impactful advancements in this realm is the development of performance analytics, which uses data-driven insights to improve athletic performance. Through the integration of wearable devices, motion tracking systems, and advanced data analysis techniques, coaches and athletes can now monitor performance in real-time and make informed decisions to enhance training programs. This article explores the evolving role of technology in sports, focusing on the future of performance analytics and coaching. It examines how technologies such as GPS trackers, biometric sensors, and video analysis tools are reshaping coaching strategies, optimizing athlete development, and providing a more precise understanding of individual performance. Furthermore, the article discusses the ethical considerations and challenges that come with the use of advanced technology in sports, including issues related to data privacy, fairness, and the potential for over-reliance on technology. As technology continues to advance, the future of sports coaching will likely see an even deeper integration of AI, machine learning, and predictive analytics to further refine performance outcomes and provide personalized training regimens.